Environmental taxation and the double dividend - Mooij, Ruud A. de (Contributions to economic analysis ;, 2000)
Environmental Taxation and the Double Dividend explores the welfare effects of environmental taxes in a second-best framework. It starts from a benchmark model which reveals that environmental taxes typically exacerbate pre-existing tax distortions, even if the revenues are used to cut other distortionary taxes. Subsequent chapters extend the benchmark model by introducing capital, terms of trade effects, transfers, involuntary unemployment, or environmental feedbacks. Thus, the book reveals several channels through which a double-dividend can be obtained. However, it also shows the trade-offs they induce. Simulations with the models illustrate the importance of these trade-offs for European economies. This book is a useful tool for graduates, post graduates, researchers and staff of universities with fiscal and environmental departments. International organizations such as the IMF, OECD and the World Bank, and policy makers within governments: Ministries of Finance/Economics/Environment. Research Institutes, both private and public will also benefit from this piece of work.